Role of Vegetarianism, Smoking, and Hydroxocobalamin in Optic Neuritis - Wadia, N. H. (1972)
Only 20 patients with optic neuritis of unknown aetiology could be collected in Bombay over a period of two and a half years. Only six of them were smokers and only three (one a non-smoker) had bilateral centrocaecal scotomata similar to those found in tobacco amblyopia. In 11 untreated patients the serum vitamin B(12) and plasma thiocyanate levels were estimated and found to show no significant differences from those in normal control subjects. Treatment with hydroxocobalamin in the majority of cases and with cyanocobalamin, corticotrophin, or prednisolone in the rest showed equally good results; spontaneous improvement was seen in one case. No significant role could be assigned to smoking (cyanide) or to vegetarianism in the production of optic neuritis in these patients; nor was there any evidence of depletion of total (cyanide-extracted) B(12) or of an increase in the proportion of non-cyanide-extracted B(12) in the serum.